GABA and muscimol inhibit the release of prolactin from dispersed rat anterior pituitary cells. - Grossman, A; Delitala, G; Yeo, T; Besser, G (1981)
Prolactin release from columns of dispersed rat anterior pituitary cells was inhibited by GABA and the GABA agonist muscimol. The log dose-response curves for GABA and muscimol appeared to be parallel, but were not parallel to that for dopamine. Two GABA antagonists, bicuculline and picrotoxin, blocked the action of both GABA and muscimol, but the dopamine antagonists metoclopramide and perphenazine did not. The data suggest that there are specific GABA receptors on pituitary lactotrophs.